Post a New Question


posted by .

Can someone show me step by step how to do this problem to have an example to go by so I will be able to do my other problems. Thanks

Solve by substitution


I know that you have solve one of the equations. I have picked the second one so it would be y= -1/3+1/3x right??
Then I substitute 4x-12(-1/3+1/3x)=5.
Now I have no clue what to do from there. Please help.

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.If that right?

In the bottom, rearrange to read
x= 3y+1
Now put that value for x in the top equation...
4( 3y+1)-12y=5
then solve for y.

when you get y, go back and put it in
x= 3y+1 to get x.

I suggest you show your number as
Then 4x -12[(x-1)/3] = 5
Then 4x -4(x-1) = 5
etc. I'm sure you can handle it from here.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question